PENGARUH LAYANAN INFORMASI TENTANG PEMAHAMAN DIRI TERHADAP SISWA SELF EFFICACY RENDAH KELAS X SOSIAL SMA NEGERI 12 PEKANBARU TAHUN AJARAN 2013 – 2014 - Desy Nilmala Sari; Raja Arlizon; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This research to determine the effect ofservice information about self understandingof low self efficacy students class X Social SMA N 12 Pekanbaru academic year 2013-2014. Subjects were students of class X Social are low self efficacy .This research method is Quasy Experimental Research design. To determine differences in level self efficacy of students before and after information service about self understanding then use the pre experimental design One-Group Pretest-Posttest Design. Data collection tool used was a questionnaire. Where samples were 31 people with a total sample technique. The description of the levels self efficacy of students before information service about self understanding given all of students in the low category. The description of the levels self efficacy student after information service about self understanding given average students in Class X Social SMA N 12 Pekanbaru in highter category. Based on the analysis of data by using the ttest and ttable (12.33> 2.021) than the results of the calculation of the determinant of the correlation coefficient r2 = 0.42 was obtained, which means there is a 42% contribution to the increasing level self efficacy of information service about self understanding student of class X Social SMA N 12 Pekanbaru academic year 2013-2014.Key words: information service , Self efficacy,self understanding